THE THEMATIC FIELD WITH THE FEATURE “DEVIATION FROM THE NORM” IN THE RUSSIAN LANGUAGE - Ulugoy Avazovna Khamrayeva (Bright Mind Publishing, 2026)
The article examines the thematic field with the feature “deviation from the norm” in the Russian language as an important component of the lexical-semantic system. It represents a structured set of evaluative lexical units reflecting cultural values, social expectations, and collective notions of normality. The analysis shows that deviation from the norm is conceptualized through metaphor, expressive word-formation, and evaluative semantics. The main lexical-semantic groups, their negative connotation, and pragmatic orientation are identified.
Keywords: Deviation from the norm, thematic field, evaluative lexicon, semantic analysis, Russian language, cultural values, metaphor, word-formation, pragmatics, axiology.